Escherichia coli stress response systems and their reaction to terahertz radiation - S. E. Peltek; E. V. Demidova; V. M. Popik; T. N. Goryachkovskaya (Вавиловский журнал генетики и селекции)
In this review, we summarize the latest data concerning the reactions of Escherichia coli to nonthermal terahertz radiation and the underlying molecular mechanisms. E. coli is the most simple and convenient model object for studying the effects of terahertz radiation: both its genetics and metabolism are well studied, and it is easily amenable to genetic engineering allowing one to create biosensors using promoters of genes activated by certain stress factors and the reporter GFP protein. Transformed E. coli cells containing biosensors can be used to visualize their reactions to terahertz radiation based on the intensity of GFP fluorescence. In this review, we present data on the response of certain E. сoli stress response systems to terahertz radiation obtained by us, as well as by other authors. We discuss experimental results for E. сoli/ pKatG-GFP, E. сoli/pCopA-GFP, and E. сoli/ pEmrR-GFP biosensors that are used to detect E. сoli genetic networks responding to oxidative stress, copper ion homeostasis failures, and antiseptics, respectively. The obtained data indicate that exposure to nonthermal terahertz radiation induces E. сoli gene networks of oxidative stress and copper ion homeostasis, but does not activate those responding to antibiotics, protonophores, or superoxide anions. The fact that E. сoli/pKatG-GFP and E. сoli/pCopA-GFP biosensors have different activation and reaction periods when exposed to terahertz radiation and natural inducers suggests that reactions of oxidative stress and copper ion homeostasis systems to terahertz radiation are specific.